Measurement of Customer Satisfaction Using Operational Reliability and Responsiveness to Customers of KSPPS BMT Assyafi'iyah Berkah Nasional, Pekalongan Branch - Suharto Suharto; Siti Lela Nurmarlina; Nani Septiana (Universitas Muhammadiyah Metro, 2021)
This study aims to analyze the effect of operational reliability the responsiveness on customer satisfaction. Coincidence sampling technique was used to obtain a sample of 85 respondents. The terms of the instrument test use validity and reliability tests. The requirements are normal liliefors, homogeneity, linearity, and regression significance must be met while the analysis of the model used is a structural equation, namely Structural Equation Modeling.The findings of this study are that there is a direct positive effect of operational reliability on responsiveness, there is a direct effect of operational reliability on customer satisfaction, and there is a direct effect of responsiveness on customer satisfaction.